ANDROID MOBILE-BASED ENGLISH LEARNING GAME EDUCATION FOR CHILDREN IN INDONESIA - Devi Afriyantari Puspa Putri; Diah Priyawati; Nur Khaulah Arrizka; Fadilla Setia Khasanah; Inesti Litaswari (Jurnal Teknik Informatika (Jutif), 2023)
The increasing use of english languange and its importance as a global languange make english languange become important to learn and understand by many people. However, there are some difficulties in learning English, especially for early childhood in Indonesia, due to various factors, including: lack of vocabulary, and teaching materials and books that are less innovative. Therefore, this study aims to build an edugame that contains animal and fruit vocabulary for early childhood in Indonesia based on the CCI guidelines to make applications that are quite innovative. The ADDIE method was chosen as the research method used which consists of: pre-production, production, and post-production. The edugame application in this reseacrh contains of two main menus, are: learning menu that contain fruits and animal vocabularies alongside with sound of their spelling, and play game menu, that challenge children to guess the correct answer of every vocabulary. According to the result of pretest and posttet test that conducted on 40 children with parental assistance showed the increasing of scores in answering list of questions. Besides that, the SUS testing carried out in this research got an average point about 84.81 which means that the applicatian has a good function and can be accepted by users.